(3CQLhRI aj GdTWQfLs ((3ESeGYjd Hf eMeO s)
(3ChdgG (B:s
(3aUd ai ehVY GdTWQfL heG ajg ef GdMce bjd gh YbdGf eJLGOdGf hLjTGf eJbGHdGf JLeYge QGbYI GdLdhO s
(3BNQgG (B:s
(3bO QeRhg ddgOi eKGdkG Cf GdMcje jVQH GdCeKGdG hgPg NGJeI GdCQLhRI heG MhJ ef Mcje YRjRg hHJeGeg Je GdcJGH HMeO Gddg GdcQje GdhgGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs